The Effect of Service Learning on the Prosocial Behavior of Islamic Boarding School Students - Zamzami Sabiq; Fattah Hanurawan; Imanuel Hitipeuw (SYAMIL: Journal of Islamic Education, 2024)
This study aims to reveal the effect of service learning on students' prosocial behaviour in boarding schools. A quantitative research approach with a quasi-experimental research design was used in this study. Researchers chose to use a non-equivalent pretest-posttest control group design, which is a design that measures the behaviour of the experimental group and control group before and after treatment. The population in this study were Santri Pondok Pesantren Sabilul Ihsan Pamekasan with the characteristics of boarding students and following the study of Kitab Bidayatul Hidayah. Total sampling was carried out because the population in the study was small, then grouped into experimental groups and control groups. The collected data were analyzed using analysis of covariance (ANOVA) with the SPSS 16 for Windows program. From the analysis that has been done, the results of this study indicate that (1) There are differences in the prosocial behaviour of boarding school students before and after the application of the service learning method in the experimental class. (2) The application of the service learning method is more effective than the bandongan method to improve the students' prosocial behaviour. The results found that service learning had a greater effect on the prosocial behaviour of boarding school students in the experimental group than the students in the control group. The application of service learning conducted in the experimental group was able to increase the prosocial behaviour of students with an effective contribution of 50.1 per cent.